Nuprl Lemma : alternating-series-converges-ext
∀x:ℕ ⟶ ℝ. ((∃M:ℕ. ∀n:ℕ. (M < n 
⇒ ((r0 ≤ x[n]) ∧ (x[n + 1] ≤ x[n])))) 
⇒ lim n→∞.x[n] = r0 
⇒ Σn.-1^n * x[n]↓)
Proof
Definitions occuring in Statement : 
series-converges: Σn.x[n]↓
, 
converges-to: lim n→∞.x[n] = y
, 
rleq: x ≤ y
, 
int-rmul: k1 * a
, 
int-to-real: r(n)
, 
real: ℝ
, 
fastexp: i^n
, 
nat: ℕ
, 
less_than: a < b
, 
so_apply: x[s]
, 
all: ∀x:A. B[x]
, 
exists: ∃x:A. B[x]
, 
implies: P 
⇒ Q
, 
and: P ∧ Q
, 
function: x:A ⟶ B[x]
, 
add: n + m
, 
minus: -n
, 
natural_number: $n
Definitions unfolded in proof : 
member: t ∈ T
, 
so_apply: x[s]
, 
int-rmul: k1 * a
, 
so_lambda: λ2x.t[x]
, 
accelerate: accelerate(k;f)
, 
alternating-series-converges, 
converges-iff-cauchy-ext
Lemmas referenced : 
alternating-series-converges, 
converges-iff-cauchy-ext
Rules used in proof : 
introduction, 
sqequalSubstitution, 
sqequalTransitivity, 
computationStep, 
sqequalReflexivity, 
cut, 
instantiate, 
extract_by_obid, 
hypothesis, 
sqequalRule, 
thin, 
sqequalHypSubstitution, 
equalityTransitivity, 
equalitySymmetry
Latex:
\mforall{}x:\mBbbN{}  {}\mrightarrow{}  \mBbbR{}
    ((\mexists{}M:\mBbbN{}.  \mforall{}n:\mBbbN{}.  (M  <  n  {}\mRightarrow{}  ((r0  \mleq{}  x[n])  \mwedge{}  (x[n  +  1]  \mleq{}  x[n]))))
    {}\mRightarrow{}  lim  n\mrightarrow{}\minfty{}.x[n]  =  r0
    {}\mRightarrow{}  \mSigma{}n.-1\^{}n  *  x[n]\mdownarrow{})
Date html generated:
2019_10_29-AM-10_29_52
Last ObjectModification:
2019_04_02-AM-10_56_57
Theory : reals
Home
Index